Data Security and Cryptography Substitution Techniques Algorithms implementation (The International Journal of Engineering & Information Technology (IJEIT), 2024)
Cryptography and data security have been usedto make data more secure for many years, militarycommunications are having a major impact on growingcryptography field. Although the internet have been invitedin the ends 1960's, but it is not appear to public until inventthe World Wide Web (www) in 1989. The World Wide Weballows people to e-mail each other and transfer data. Thisappeared as one reason in growing use of computer. Inaddition needs to make e-commerce more secure.Cryptography understanding helps to find better ways orprotocols to make transfer data faster and more efficient.This paper starts with a brief background about securityand cryptography. It provides central concepts ofcryptography. Also provides an account of substitutiontechniques algorithms and their implementation. Theimplementation will be as an application in c# language thatreads a text, encodes it by a specified algorithm and decodesthe encrypted text. In addition explaining the mathematicalfunctions used in the algorithms